If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = -3x + -7 Reorder the terms: -7 + x = -3x + -7 Reorder the terms: -7 + x = -7 + -3x Add '7' to each side of the equation. -7 + 7 + x = -7 + 7 + -3x Combine like terms: -7 + 7 = 0 0 + x = -7 + 7 + -3x x = -7 + 7 + -3x Combine like terms: -7 + 7 = 0 x = 0 + -3x x = -3x Solving x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. x + 3x = -3x + 3x Combine like terms: x + 3x = 4x 4x = -3x + 3x Combine like terms: -3x + 3x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 4b(6-5b)= | | -5(3n+5)=2 | | x-27=8x+57 | | 11-7x=3-8x | | 7(8+3h)= | | 42/5+42/6 | | y=3+-4x | | x/3+x/2=8/3 | | -x^2+10x+128=0 | | 11x-45=4x+39 | | 2y=24x+2 | | -4(2y-8)-y=-3(y-3) | | 5/6z=5/8 | | x^2-4x+64=0 | | (-a-7b+3)6ab= | | 25x+-6x+120=21x | | ax-7b=4c | | 2x-5(4x+10)=58 | | (3x-4)(3x-4)+16=0 | | (x-8)(x-8)-81=0 | | y/5+y/4=7/5 | | -4(6y-5)-y=-3(y-2) | | 4k^2+12K-9=0 | | 1/5x+1/4=-2 | | 5/12X=3 | | 3/8X=24 | | 1/2X=11 | | 36r*5= | | -2y-7(6y-8)=1+9(1-y) | | E=LR+Lr | | 4/9X=20/18 | | r+6=3(r-3) |